Fast recognition of partial star products and quasi cartesian products - Hellmuth, Marc (Ars mathematica contemporanea, 2015)
This paper is concerned with the fast computation of a relation ?$\mathfrak{d}$? on the edge set of connected graphs that plays a decisive role in the recognition of approximate Cartesian products, the weak reconstruction of Cartesian products, and the recognition of Cartesian graph bundles with a triangle free basis. A special case of ?$\mathfrak{d}$? is the relation ?$δ^*$?, whose convex closure yields the product relation ?$δ$? that induces the prime factor decomposition of connected graphs with respect to the Cartesian product. For the construction of ?$\mathfrak{d}$? so-called Partial Star Products are of particular interest. Several special data structures are used that allow to compute Partial Star Products in constant time. These computations are tuned to the recognition of approximate graph products, but also lead to a linear time algorithm for the computation of ?$δ^*$? for graphs with maximum bounded degree. Furthermore, we define quasi Cartesian products as graphs with non-trivial ?$δ^*$?. We provide several examples, and show that quasi Cartesian products can be recognized in linear time for graphs with bounded maximum degree. Finally, we note that quasi products can be recognized i n sublinear time with a parallelized algorithm.
Keywords: approximate product; aproksimativni produkt; Cartesian product; grafovski sveženj; graph bundle; kartezični produkt; kvazi produkt; parcialno zvezdni produkt; partial star product; product relation; produktna relacija; quasi product